Multiparametric and multilevel characterization of morphological alterations in patients with transient ischemic attack. Issue 7 (19th January 2021) - Lv, Yating; Wei, Wei; Han, Xiujie; Song, Yulin; Han, Yu; Zhou, Chengshu; Zhou, Dan; Zhang, Fuding; Wu, Xiaoyan; Liu, Jinling; Zhao, Lijuan; Zhang, Cairong; et al.
Abstract: Transient ischemic attack (TIA), an important risk factor for stroke, is associated with widespread disruptions of functional brain architecture. However, TIA‐related structural alterations are not well established. By analyzing structural MRI data from 50 TIA patients versus 40 healthy controls (HCs), here we systematically investigated TIA‐related morphological alterations in multiple cortical surface‐based indices (cortical thickness [CT], fractal dimension [FD], gyrification index [GI], and sulcal depth [SD]) at multiple levels (local topography, interregional connectivity and whole‐brain network topology). For the observed alterations, their associations with clinical risk factors and abilities as diagnostic and prognostic biomarkers were further examined. We found that compared with the HCs, the TIA patients showed widespread morphological alterations and the alterations depended on choices of morphological index and analytical level. Specifically, the patients exhibited: (a) regional CT decreases in the transverse temporal gyrus and lateral sulcus; (b) impaired FD‐ and GI‐based connectivity mainly involving visual, somatomotor and ventral attention networks and interhemispheric connections; and (c) altered GI‐based whole‐brain network efficiency and decreased FD‐based nodal centrality in the middle frontal gyrus. Moreover, the impaired morphological connectivity showed high sensitivities and specificities for distinguishing the patients from HCs. Altogether, these findings demonstrate the emergence of morphological index‐dependent and analytical level‐specific alterations in TIA, which provide novel insights into neurobiological mechanisms underlying TIA and may serve as potential biomarkers to help diagnosis of the disease. Meanwhile, our findings highlight the necessity of using multiparametric and multilevel approaches for a complete mapping of cerebral morphology in health and disease. Abstract : Transient ischemic attack is associated with widespread morphological alterations and the alterations depend on choices of morphological index and analytical level. Altered local topography is detected only in cortical thickness. Impaired connectivity and disrupted topology exist only in folding‐based networks.